Diaphragmatic dysfunction: an unusual complication in HELLP syndrome - Sharma, Manoj Kumar (International Journal of Advances in Medicine, 2018)
Diaphragmatic dysfunction in HELLP [hemolysis (H), elevated liver enzymes (EL), low platelet count (LP)] Syndrome and Diaphragmatic dysfunction is an uncommonly reported association, wherein, patients who develop acute respiratory insufficiency poses a delay in weaning without any obvious cause. A high degree of clinical suspicion of sepsis induced diaphragmatic dysfunction needs to be kept in mind by the clinicians dealing with cases of HELLP Syndrome who may develop acute respiratory insufficiency without definite predisposing factors.